Implementing pseudo haptic feedback in a semi-isometric master interface for robotic surgery. (11th October 2017) - Kim, In; Tadano, Kotaro; Kanno, Takahiro; Kawashima, Kenji
We have developed a master interface that uses an isometric velocity control technique for translation and an anisometric position control technique for rotation. Using the developed interface, the operator can concentrate on the slave side and control the robot without repositioning required in conventional master arm due to the workspace limitation. However, it cannot display haptic to the operator for the translation directions with the manipulator. In this article, we propose a method to feedback the external force on the slave side to the master manipulator without using actuators or link mechanism but using a pseudo haptic effect. A flexible wrist joint with a spring is used at the tip of the slave forceps to enhance visual effect. The spring stiffness is pneumatically controlled. At the same time, we change the reference velocity of the slave according to the external force applied to the slave manipulator. The changed velocity caused by the external force restrains the slave motion. Using both the visual feedback and the motion restrain, the master–slave system is able to display force to the operator as pseudo haptic feedback without actuators. Experiments of pulling suture threads are executed using the developed master–slave surgical robot. It is confirmed that the master–slave system with pseudo haptic feedback can decrease the variance of force.